A history of mild shocks experienced by the regolith particles on hydrated asteroid Ryugu - Tomioka, Naotaka; Yamaguchi, Akira; Ito, Motoo; Uesugi, Masayuki; Imae, Naoya; Shirai, Naoki; Ohigashi, Takuji; Kimura, Makoto; Liu, Ming-Chang; Greenwood, Richard C.; Uesugi, Kentaro; Nakato, Aiko; et al. (Nature astronomy, 2023)
Micrometeorites, a possible major source of Earth’s water, are thought to form from explosive dispersal of hydrated chondritic materials during impact events on their parental asteroids. However, this provenance and formation mechanism have yet to be directly confirmed using asteroid returned samples. Here, we report evidence of mild shock metamorphism in the surface particles of asteroid Ryugu based on electron microscopy. All particles are dominated by phyllosilicates but lack dehydration textures, which are indicative of shock-heating temperatures below ~500 °C. Microfault-like textures associated with extensively shock-deformed framboidal magnetites and a high-pressure polymorph of Fe–Cr–sulfide have been identified. These findings indicate that the average peak pressure was ~2 GPa. The vast majority of ejecta formed during impact on Ryugu-like asteroids would be hydrated materials, larger than a millimetre, originating far from the impact point. These characteristics are inconsistent with current micrometeorite production models, and consequently, a new formation mechanism is required. Signatures of impact-induced shocks are found on Ryugu returned particles. Observations show that they happened at moderate temperatures (~500 °C) and pressures (~2 GPa) and did not dehydrate the particles substantially, suggesting that bigger meteoroids, rather than micrometeoroids, provide Earth with hydrated minerals.